Vicarious Liability in Indonesian Telemedicine: Reconstructing the Legal Status of Digital Health Platforms - Rizka Erlyani; Abdul Kolib; Handar Subhandi Bakhtiar (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The rapid expansion of telemedicine in Indonesia has transformed healthcare delivery from a facility-based model into a platform-based ecosystem in which digital health platforms directly connect patients and medical professionals. However, Indonesian health regulations continue to position digital platforms merely as electronic system providers or cooperation partners of healthcare facilities, despite their substantial operational control over healthcare services. This study examined the legal status and liability of digital health platform providers in Indonesian telemedicine services. The research employed normative juridical methods using statutory, conceptual, and comparative approaches. The findings revealed that digital health platforms simultaneously function as electronic system providers, service business actors, and personal data controllers under different regulatory regimes, while lacking explicit recognition as healthcare service providers. This regulatory fragmentation creates accountability gaps, particularly when patients suffer losses arising from telemedicine services. The study argued that liability-shifting clauses commonly used by digital health platforms are inconsistent with consumer protection principles and the doctrine of vicarious liability under Article 1367 of the Indonesian Civil Code. Accordingly, this article proposed a vicarious liability model that imposes legal responsibility on digital platforms as the controlling party over medical professionals operating under the platform's operational ecosystem, supported by co-regulation principles and integrated cross-institutional supervision.